New frames of reference for mapping drugs in the four classes of the BCS and BDDCS into regions with clear boundaries. Issue 11 (3rd September 2015) - Chatzizacharia, Kalliopi; Hatziavramidis, Dimitris
<x xml:space="preserve">Abstract</x> The Biopharmaceutics Classification System (BCS), adopted by drug regulatory agencies for oral drug products approval, classify drug substances into four classes according to their aqueous solubility and epithelial membrane permeability. In a solubility‐permeability frame of reference, drugs on the boundaries of the four regions depicting the four drug classes are problematic to classify. To remove the fuzziness in the boundaries of the solubility‐permeability frame of reference, a dataset of 85 oral drugs from all four classes of BCS are mapped into new frames of references in which the coordinate axes are based on the rates of dissolution, systemic elimination (metabolism), and membrane permeation. © 2015 American Institute of Chemical Engineers AIChE J, 61: 3570–3579, 2015